Lattice Boltzmann simulation of the movement of droplets on stripe-patterned surfaces having different wettability. (January 2016) - Lee, Changwoo; Lyu, Sungnam; Park, Jae Wan; Hwang, Woonbong
Highlights: We performed Lattice Boltzmann simulations of droplet movement of patterned surface. Bond number and interparticle strengths are determined for the simulation. The critical angle which droplet starts to move is affected by Bond number and thickness of the stripes. Abstract: A stripe-patterned surface with different wettability can be effective for the passive control of droplet movement on a vertical surface. We have performed three-dimensional Lattice Boltzmann (LB) simulations to investigate the effect of the pattern characteristics and liquid properties on the droplet movement. The simulation was initiated by imposing gravity on the droplet formed on the surface. The droplet moves along the direction of the pattern when the angle between the gravity and the pattern is small; however, it starts to overrun the stripes when the angle is greater than a certain value, i.e., critical angle. It is shown that the critical angle decreases as the Bond number increases while it increases as the strength of the adhesion/repulsion force increases. The droplet forms a curved asymmetric boundary on the stripe-patterned surface due to gravity and surface forces. The critical angle is also affected by the thickness of the stripes.